Mesenchymal stem cell therapy for osteoarthritis: current perspectives - Wyles CC (Dove Medical Press, 2015)
Cody C Wyles,1 Matthew T Houdek,2 Atta Behfar,3 Rafael J Sierra,21Mayo Medical School, 2Department of Orthopedic Surgery, 3Division of Cardiovascular Diseases, Mayo Clinic, Rochester, MN, USAAbstract: Osteoarthritis (OA) is a painful chronic condition with a significant impact on quality of life. The societal burden imposed by OA is increasing in parallel with the aging population; however, no therapies have demonstrated efficacy in preventing the progression of this degenerative joint disease. Current mainstays of therapy include activity modification, conservative pain management strategies, weight loss, and if necessary, replacement of the affected joint. Mesenchymal stem cells (MSCs) are a multipotent endogenous population of progenitors capable of differentiation to musculoskeletal tissues. MSCs have a well-documented immunomodulatory role, managing the inflammatory response primarily through paracrine signaling. Given these properties, MSCs have been proposed as a potential regenerative cell therapy source for patients with OA. Research efforts are focused on determining the ideal source for derivation, as MSCs are native to several tissues. Furthermore, optimizing the mode of delivery remains a challenge both for appropriate localization of MSCs and for directed guidance toward stemming the local inflammatory process and initiating a regenerative response. Scaffolds and matrices with growth factor adjuvants may prove critical in this effort. The purpose of this review is to summarize the current state of MSC-based therapeutics for OA and discuss potential barriers that must be overcome for successful implementation of cell-based therapy as a routine treatment strategy in orthopedics.Keywords: mesenchymal stem cell, osteoarthritis, treatment, regenerative medicine, cell therapy